2024
DOI: 10.2174/1570159x20666220927092016
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effects of Short-Chain Fatty Acids on Chronic Pain

Abstract: The intestinal homeostasis maintained by the gut microbiome and relevant metabolites is essential for health, and its disturbance leads to various intestinal or extraintestinal diseases. Recent studies suggest that gut microbiome-derived metabolites short-chain fatty acids (SCFAs) are involved in different neurological disorders (such as chronic pain). SCFAs are produced by bacterial fermentation of dietary fibers in the gut and contribute to multiple host processes, including gastrointestinal regulation, card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…Interestingly, through a comparative analysis of potential causally related bacterial genera in NP and TSP, Butyrivibrio was identified as a shared potential protective genus. Its production of butyrate, propionate, and other SCFAs inhibiting histone deacetylase activity may be one of the potential mechanisms underlying Butyrivibrio ’s analgesic effects ( Descalzi et al, 2015 ; Tang et al, 2022 ). Research on the relationship between gut microbiota and low back pain or/and lower limb pain is more abundant.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, through a comparative analysis of potential causally related bacterial genera in NP and TSP, Butyrivibrio was identified as a shared potential protective genus. Its production of butyrate, propionate, and other SCFAs inhibiting histone deacetylase activity may be one of the potential mechanisms underlying Butyrivibrio ’s analgesic effects ( Descalzi et al, 2015 ; Tang et al, 2022 ). Research on the relationship between gut microbiota and low back pain or/and lower limb pain is more abundant.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Cryan JF and Dinan TG suggested that probiotics play a role in improving pain in animals, and preliminarily revealed the mechanism of the microbiota-gut-brain axis [24]. Verdu et al revealed that specific probiotic therapy attenuates antibiotic-induced visceral hypersensitivity in mice through modulating sensory neurotransmitter content (substance P) in the colon and altering visceral perception [29], while Tang et al stated that SCFAs (produced with the bacterial fermentation of dietary fibers in the gut) are implicated in the modulation of chronic pain through several possible mechanisms [53]. Recently, Rebeca M et al revealed that improvement in abdominal pain was associated with the relative abundance of A. muciniphila in IBS patients through FMT [54], mainly because A. muciniphila is a promising next-generation probiotic that produces multiple SCFAs as end products by degrading mucus [55].…”
Section: Principal Findingsmentioning
confidence: 99%